Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XXIV): D. latilimbum, recently described from southern Xizang (Tibet), is another new synonym of D. kamaonense, a Sino-Himalayan species - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on critical observations on herbarium specimens and living plants in the wild, we demonstrate that Delphinium latilimbum, recently described from Cona county in southern Xiang (Tibet), China, is conspecific with D. kamaonense, a widely distributed Sino-Himalayan species. We therefore place D. latilimbum in synonymy with D. kamaonense herein. The occasional presence of sparsely pubescent filaments of stamens in D. kamaonense is confirmed, but this character is considered to be of little taxonomic significance. A distribution map is given for D. kamaonense.